Development of nuclear energy in the Republic of Uzbekistan - Avazov A.A.Tashkent (Genius Journals, 2022)
This article discusses the problems and prospects for the development of nuclear energy in Uzbekistan
Keywords: Nuclear Energy; Personnel Training; State Regulation